Figura” i „forma”: O funkcji obrazów w kulturze wieków średnich na przykładzie XII-wiecznych przedstawień kosmologicznych w Chronicon Zwiefaltense Minus = „FIGURE” AND „FORM” : ON THE FUNCTION OF IMAGES IN MEDIEVAL CULTURE ON THE EXAMPLE OF 12TH-CENTURY COSMOLOGICAL ILLUMINATIONS IN CHRONICON ZWIEFALTENSE MINUS - Olszewska, Anna (Studia religiologica, 2008)
The text inquires into the function and meaning of two miniatures in the 12th-century manuscript Chronicon Zwiefaltense Minus (Stuttgart, W.L.B., MS. Hist. Fol. 415; 1138-1147). They are two page-sized compositions on cosmological subjects printed on a single leaf in the manuscript (folio 17). They are a picture of the creation of the world and a complex image of time rendered in cycles. I study the composition of both miniatures and relative placement of their elements. Then I analyze their iconography based on a Medieval alegoresis of visions of the world. These interpretations lead to the conclusion that both pictures make up a thematic and formal whole. They are an example of an extraordinarily refi ed use of visual forms conveying a theological commentary to Genesis. It is possible to verify this interpretation by considering what purpose the diptych might have served inserted in a short compilation of texts on astronomy, which is the subject of the last part of the article. I point to the notions figura and formatione with which both miniatures are introduced in the text of Chronicon Zwiefaltense Minus and go on to quote some examples of how such references were understood in the writings of Hugo of St. Victor and Honorius of Autun. In this light, the diptych appears to be an attempt to visualize not so much the figures of time or of creation, but the forming process of universal order. Both images were created to replace a verbal expression as was the case in texts like De Arca Noe Mystica by Hugo of St. Victor. This time, the chosen medium was a picture employing special personifications to combine inscriptions, iconographic themes, all appropriately spaced respective to the rest.